Prey - Schachner, Sarah (Leonine Distribution GmbH, 2023)
The epic Predator legacy continues with this action-thriller set in the Comanche Nation. When Naru, a fierce and highly skilled young warrior, sets out to protect her people, the prey she stalks turns out to be a highly evolved alien predator leading to a vicious and terrifying showdown
Spielfilm. USA. 2022
Enthält die Comanche Tonspur in voller Länge zusätzlich zu Deutsch & Englisch
Bildformat 2.39:1 (16:9)
Keywords: Science fiction films; Thrillers; Action films; Thriller; Actionfilm; Science-Fiction-Film; Human-alien encounters / Drama; Extraterrestrial beings / Drama; Comanche Indians / Drama; Predators (Fictitious characters : Dark Horse comics) / Drama; Fiction films; Feature films; Thrillers (Motion pictures); Video recordings for the hearing impaired; Action and adventure films; Video recordings for people with visual disabilities; Films d'aventures; Thrillers (Films); Films de science-fiction; Films de fiction; Vidéos pour personnes handicapées auditives; Vidéos pour personnes handicapées visuelles; Film; DVD-Video